Novel experiment design for unmanned aerial vehicle controller performance testing - Dim, Cherub (Animo Repository, 2019)
Unmanned Aerial Vehicles (UAV) are becoming popular to the innovating world. This paper presents a novel experiment design to determine the performance of UAV control system. The hardware platform developed is composed of a quadcopter with a multipurpose autopilot system. While the experimental design considers both quantitative and qualitative aspects of the controller. The qualitative components dealt with the hardware compatibility, acceptability and license. On the other hand, the quantitative component measured the accuracy of waypoints, altitude hold and loiter performance of the UAV. The results shows that the new experiment design platform was able to compare two popular autopilot software in terms of performance and acceptability. © Published under licence by IOP Publishing Ltd.